Prostate tumour originating from interstitial cells of Cajal: a case presentation and review of the literature - Grotthuss, Gerard; Poletajew, Slawomir; Dzik, Tomasz; Borówka, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2011)
We present a case of an extremely rare, atypical prostate tumour, diagnosed in a 57-year-old man, who reported pain in the pelvic area, problems with defecation and lower urinary tract symptoms (LUTS). A giant prostate tumour was diagnosed in computed tomography. The histopathological examination findings from core needle biopsy of multiple sites were not unequivocal. The patient underwent pelvic exenterative surgery. Also Bricker ileal conduit urinary diversion and sigmoidostomy were performed. Histopathological examination of the surgical specimen revealed a gastrointestinal stromal tumour originating from the prostate and infiltrating the urinary bladder and the rectum. The patient was qualified for systemic adjuvant chemotherapy, but he did not give his consent to that treatment. Clinical evaluation at 6 months following the surgery revealed major improvement in the patient’s health status, but the patient still rejects adjuvant treatment. The paper also presents an overview of the literature on gastrointestinal stromal tumour (GIST) of the prostate.